ORGANIZATIONAL CITIZENSHIP BEHAVIOUR MEDIATES LEADERSHIP STYLE AND ORGANISATIONAL CULTURE ON EMPLOYEE PERFORMANCE - Nur, Mustika; Rossanty, Niluh Putu Evvy; Kadang, Juliana (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2025)
Empirically, the study aims to empirically test (1) the effect of leadership style on employee performance at the Office of Public Works, Spatial Planning, Housing, Tojo Una-Una Regency (2) Effect of Organizational Culture on Employee Performance (3) Effect of Leadership Style on Organizational Citizenship Behavior (OCB) (4) Effect of Organizational Culture on Organizational Citizenship Behavior (OCB) (5) Effect of Organizational Citizenship Behavior (OCB) on Employee Performance (6) Effect of Leadership Style on Employee Performance through Organizational Citizenship Behavior (OCB) (7) Effect of Organizational Culture on Employee Performance through Organizational Citizenship Behavior (OCB). This type of research is included in Explanatory or Confirmatory Research. Hypothesis testing using PLS-SEM with a sample of 161 respondents consisting of civil servants and non-civil servants. The results of the analysis show that hypotheses 1-5 for direct effect testing and hypotheses 6-7 for indirect effect testing with the provisions of P-Values <0.05 and t-value> 1.97.